KONDISI EXISTING SOSIAL EKONOMI DAN BUDAYA MASYARAKAT SEKITAR PERTAMBANGAN BATUBARA DI KECAMATAN ANGSANA KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Septrianetha Septrianetha; Emmy Lilimantik; Achmad Syamsu Hidayat; Suyanto Suyanto (EnviroScienteae, 2022)
The presence of mining companies is expected to bring benefits and prosperity to the surrounding community. Angsana District, Tanah Bumbu Regency has several coal mining companies operating. The intent of research is to know the existing social, economic and cultural conditions of the community around coal mining. The research method is statistical test calculation method and interactive model (Miles and Hubermen). Sampling and Observation through data collection using interviews and documentation with observations in Angsana District, on Ring I, Ring II and Ring III of the research area. Result : Ring III community income level is higher than Ring I and Ring II, social conditions have a relatively positive and negative impact, cultural conditions have little influence. The conclusion is that the existing social, economic and cultural conditions around coal mining in Angsana District have increased.